BRCA2 mutation in advanced lung squamous cell carcinoma treated with Olaparib and a PD-1 inhibitor: a case report - Chen, Zhujun; Wang, Kang; Zhao, Lintao; Gong, Liang (Frontiers in Oncology, 2023)
Background: Mutations in the human breast cancer susceptibility gene 2 (breast cancer 2, BRCA2) increase the risk of breast, ovarian and other cancers. Olaparib, an oral poly[adenosine diphosphate (ADP)–ribose] polymerase (PARP) inhibitor, is usually prescribed to treat BRCA mutated tumors, especially breast and ovarian cancers. Programmed cell death-1 (PD-1) inhibitors have revolutionized the treatment of lung cancer and many other cancers by destroying the interaction between receptors with ligands in the tumor-immune microenvironment and enabling T cells to recognize and attack cancer cells. Case description: In our study, we report a patient with advanced BRCA2 lung squamous cell carcinoma who received platinum-based chemotherapy combined with paclitaxel. Seven months later, the disease progressed. BRCA2 mutations were detected in peripheral blood by next-generation sequencing. After 2 months of treatment with Olaparib combined with Cindilimab, the patient was in partial remission and the progression-free survival (PFS) lasted for 6 months, but the patient developed immune renal damage. Conclusions: This study adds to the clinical data for the treatment of BRCA2 mutant non-small cell lung cancer by demonstrating that lung squamous cell carcinoma has a good response to PARP inhibitors. It also serves as a reminder that there may still be some negative effects from targeted superimposed immunotherapy.